DI-047 Impact of pill burden on duration of firstline antiretroviral therapy in real life setting. (25th February 2017) - Valcarce, N; Alvarez, H; Vilariño, L; Rodriguez, I; Mariño, A
Abstract : Background: The firstline antiretroviral treatment (ART) is often considered a long term therapy at treatment initiation. The complexity of ART could influence persistence, making it shorter. Purpose: To investigate the duration of firstline ART, the main reasons for switching the firstline ART and the association between daily antiretroviral pill burden and switching. Material and methods: This was a retrospective observational study. We included all naive adult HIV infected patients who started their firstline ART in a second level hospital from January 2012 to April 2015. Duration was the time from the start of the first ART until treatment modification for any reason or last follow-up visit. Demographics and pharmacotherapeutic data were collected from electronic medical and antiretroviral dispensing records and a specific database for HIV patients. Results: 42 patients started their first ART in this period, 86% men. Median age was 43 years (IQR 33–51). 14 patients (33%) started a once daily single tablet regimen (STR): Atripla in 9 patients (64%), Eviplera in 4 patients (29%) and Stribild in 1 patient. 28 patients started a triple tablet regimen (TTR): 22 (79%) had a protease inhibitor combined with two nucleoside reverse transcriptase inhibitors and 6 (21%) had raltegravir plus a tenofovir including backbone. 71% were maintained on STR, median duration 29 months (IQR 19–40), and 39% on TTR, median duration 32 months (IQR 20–43). Firstline ART was modified in 18 patients (43%). At the time of change all patients maintained virologic suppression. In the STR group, 3 patients (21%) switched to secondline ART. Changes were for safety reasons (2 patients) and due to difficulty in swallowing (1 patient). There were 15 patients (54%) who changed in the TTR group: 11 simplifications (73%), 3 toxicity preventions (20%) and 1 drug interaction. At the end of the follow-up period, 2 patients with TTR (1 transfer to another centre and 1 death) and 1 patient with STR (transfer to another centre) discontinued ART. Conclusion: TTR was preferred as firstline ART. Median duration of the different regimens was similar and independent of pill burden. More than half of the patients on TTR switched their first ART and the main reason for change was simplification. No conflict of interest